The typologies of habitats of innovation: an analysis of the legislation in the South of Brazil under the new legal framework of science, technology and innovation. (Revista Brasileira de Contabilidade e Gestão, 2018)
This article presents a comparison between the Innovation Laws of the Southern States of Brazil (Santa Catarina, Rio Grande do Sul and Paraná) and the Federal Innovation Law in relation to the express prediction of the typologies of innovation habitats. The study reveals that states primarily support the implementation of parks and incubators. In addition, other typologies have not yet been established, reflecting the Brazilian reality in terms of the number of innovation habitats available to support entrepreneurship and innovation.
Keywords: innovation; innovation legal framework; habitats of innovation